Outcome of Sclerotherapy in a Preterm Infant with a Giant Fetal Neck Lymphatic Malformation: A Case Report - Zeng Z; Liao H; Hu F; Zhao F; Liu H; Hu Q; Yu H (Dove Medical Press, 2023)
Zhaomin Zeng,1,2 Hua Liao,1,2 Fan Hu,2,3 Fumin Zhao,2,4 Hongyan Liu,1,2 Qing Hu,1,2 Haiyan Yu1,2 1Department of Obstetrics and Gynecology, West China Second University Hospital, Sichuan University, Chengdu, People's Republic of China; 2Key Laboratory of Birth Defects and Related Diseases of Women and Children (Sichuan University), Ministry of Education, Chengdu, People's Republic of China; 3Department of Paediatric Cardiology, West China Second University Hospital, Sichuan University, Chengdu, People's Republic of China; 4Department of Radiology, West China Second University Hospital, Sichuan University, Chengdu, People's Republic of ChinaCorrespondence: Haiyan Yu, Department of Obstetrics and Gynecology, West China Second University Hospital, Key Laboratory of Birth Defects and Related Diseases of Women and Children, Sichuan University, No. 20, 3rd Section, South Renmin Road, Chengdu, Sichuan, 610041, People's Republic of China, Email fanjy422@163.comIntroduction: Lymphatic malformation (LM), most commonly present in the neck area, is benign vascular malformations of the lymphatic system. In an infant, however, LM poses a high risk of adverse outcomes.Case Presentation: We present a case with a giant fetal LM. Through ultrasonography, at 23+ weeks of gestation, a septate cystic mass 7.2× 6.5× 6.3 cm in size was found on the right side of the fetus's neck. After extensive counseling by the multidisciplinary team, the parents chose to continue the pregnancy. Severe fetal tracheal compression was observed at 29 weeks by magnetic resonance imaging (MRI). At 31 weeks and 5 days, owing to suspected fetal distress, an emergency cesarean section was performed and a male baby weighing 1720 g was delivered. The mass was 10× 16× 8 cm in size and ex utero intrapartum treatment (EXIT) was implemented. Due to progressive growth of the mass secondary to intralesional bleeding, an intralesional injection of bleomycin was administered three days later. This injection was repeated at the age of 1 month and 8 days. The baby was followed up and, by a year after his birth, LM had disappeared. The baby has since been in good health.Conclusion: Accurate prenatal diagnosis and regular monitoring of a fetus with LM may improve prognosis. It is essential to have a trained multidisciplinary team to evaluate the condition of the fetus and the neonate and to provide treatment based on the evaluation. Our experience with intralesional bleomycin injection for the treatment of a giant fetal neck LM in a preterm infant had a favorable outcome. Long-term follow-up by a multidisciplinary team is needed in such cases.Keywords: fetal lymphatic malformation, sclerotherapy, tracheal compression